Stable isotope records across the Cretaceous-Paleogene transition, Stevns Klint, Denmark: New insights from the chromium isotope system - Gilleaudeau, Geoffrey J.; Voegelin, Andrea R.; Thibault, Nicolas; Moreau, Julien; Ullmann, Clemens V.; Klaebe, Robert M.; Korte, Christoph; Frei, Robert (Geochimica et cosmochimica acta, 2018)
Late Cretaceous to Early Paleogene time represents a critical transitional period in Earth history. Global events include short-term instability in climate and ocean circulation, large igneous province emplacement, and catastrophic extinction of marine and terrestrial fauna due at least in part to a bolide impact event. The response of the ocean system to Cretaceous-Paleogene (K-Pg) global events has been the subject of much research, yet fundamental questions remain regarding carbon cycling, climate, ocean mixing, and redox conditions. To help elucidate paleoceanographic changes across the K-Pg transition, we revisit the classic Maastrichtian to Danian chalk-limestone succession at Stevns Klint, Denmark with a suite of new geochemical data, including insights from the redox-sensitive chromium isotope system. We use carbon and oxygen isotope trends to form a well-constrained framework for the succession, before presenting strontium isotope, chromium isotope, and rare-earth element data for the units deposited both before and after the K-Pg event. Carbon isotopes show only minor perturbation across the K-Pg boundary and oxygen isotopes record a prominent positive excursion, with both of these trends standing in contrast to many K-Pg boundary sections worldwide. Strontium isotopes record a spike towards more radiogenic values, which is consistent with a globally-observed, short-term weathering pulse. The chromium isotope profile of Maastrichtian chalk begins with strongly positive values followed by a sharp negative excursion associated with a facies shift and initiation of bottom currents in the Chalk Sea. δ53Cr values then recover, before falling steadily across the K-Pg boundary and into the Danian limestone. Chromium isotope trends do not correspond to changes in hydrothermal input or basin redox conditions—instead, we propose that mixing of water masses with distinct chromium isotope signatures controlled temporal chromium isotope variability. The local mixing event inferred from our Maastrichtian chromium isotope data could be related to a temporary inflow of Tethyan bottom waters, or the shift from end-Maastrichtian greenhouse warming (associated with Deccan volcanism) to the worldwide cooling phase that immediately preceded the K-Pg boundary. No immediate change in chromium isotopes is recorded across the K-Pg boundary, indicating that the bolide impactor did not substantially perturb the marine chromium cycle, at least at the scale resolvable by our data. Instead, chromium isotope trends continued to be controlled by local oceanographic processes, highlighting the potential of the chromium isotope system to record isotopic heterogeneity and mixing events in ancient oceans.